An antibacterial and antioxidant self-adhesive three-network hydrogel as well as a preparation method and application thereof
Patent Information
- Application Number
- CN202410251609.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-06
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-03-06
AI Technical Summary
但传统水凝胶也存在不足,如力学性能较差、没有粘附性、没有抗菌能力、生物相容性差等
[0019]1)本发明采用丙烯酸与聚乙二醇二丙烯酸酯通过自由基共聚形成水凝胶的第一网络,构成三网络结构水凝胶的刚性部分;重组胶原蛋白与聚丙烯酸/聚乙二醇二丙烯酸酯网络相互渗透互穿,形成水凝胶的第二网络,这种相互渗透互穿增强了水凝胶的刚性;单宁酸与硼酸通过硼酸酯键键合形成第三网络。在本发明的水凝胶中,单宁酸/硼酸、重组胶原蛋白和聚丙烯酸/聚乙二醇二丙烯酸酯之间发生非共价相互作用,在大变形下耗散能量,赋予了水凝胶很好的韧性。因而本发明的水凝胶,湿粘附能力强,延展性好。
Smart Images

Figure BDA0004727726200000051 
Figure BDA0004727726200000061 
Figure HDA0004727726210000011
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical dressing technology, specifically to an antibacterial, antioxidant, self-adhesive three-network hydrogel, its preparation method, and its application. Background Technology
[0002] The closure and repair of wounds following trauma or surgical injury are of significant clinical and research importance. Open skin / mucous membrane wounds typically require 8-12 weeks to heal. However, this orderly process can be disrupted by adverse factors such as bacterial infection, weakened immunity, excessive activity, and elevated local skin / mucous membrane temperature. To avoid these complications, a protective dressing, such as gauze, is often applied to the wound. Although a variety of wound dressings are available, they often exhibit drawbacks such as poor mechanical fit and weak adhesion to tissues. When applied to joints with high mobility, such as the wrist and elbow, it is difficult to securely cover the wound, thus failing to provide adequate protection and promote healing.
[0003] Hydrogels are a class of hydrophilic three-dimensional network polymers with physical or chemical cross-linking structures. Due to their tunable chemical and physical properties, they have become suitable materials for wound treatment and repair. However, traditional hydrogels also have shortcomings, such as poor mechanical properties, lack of adhesion, lack of antibacterial ability, and poor biocompatibility. In recent years, researchers have proposed various methods to construct multifunctional hydrogels with significant mechanical properties. In the invention patent with publication number CN 113274542 A, a hydrogel dressing that can promote wound healing is disclosed. The preparation method is to first prepare solutions of recombinant collagen, polyvinyl alcohol, tannic acid, and borax separately, then mix the tannic acid solution and borax solution evenly, add the recombinant collagen solution, and finally add the polyvinyl alcohol solution and mix well. After standing and swelling for 24 hours, an antibacterial healing gel with self-healing ability is obtained. However, the adhesion strength of this gel is not high, and the preparation is cumbersome.
[0004] The invention patent with publication number CN 115626995 A discloses a dual-network hydrogel. This hydrogel is constructed by introducing a quaternary ammonium salt modified chitosan cationic polyelectrolyte into an anionic copolymer containing propylene monomer-co-sulfonate. The first network is quaternized carboxymethyl chitosan cationic polyelectrolyte, and the second network is poly(propylene monomer-co-sulfonate) anionic polymer. This hydrogel material has excellent antibacterial and mechanical properties, with a tensile strain of up to 1100%. However, it is slightly lacking in adhesion properties, with a maximum adhesion strength to pigskin of only 6.2 kPa.
[0005] Therefore, there is a clinical need for a multifunctional hydrogel that is simple to prepare, easy and quick to operate, and has excellent mechanical properties. Summary of the Invention
[0006] The purpose of this invention is to provide an antibacterial and antioxidant hydrogel dressing that is simple to prepare, easy and quick to operate, and has high adhesion properties. This hydrogel dressing can provide strong adhesion, can be applied to joints with high mobility, and can prevent infection and promote wound healing without forming scars.
[0007] The technical solution of the present invention is as follows:
[0008] The antibacterial, antioxidant, and self-adhesive three-network hydrogel is composed of a first network formed by copolymerization of acrylic acid and polyethylene glycol diacrylate, a second network formed by interpenetration of recombinant collagen, and a third network formed by the bonding of tannic acid and boric acid through borate ester bonds.
[0009] The antibacterial, antioxidant, self-adhesive three-network hydrogel is made of the following components in the following mass ratios: 30%–35% acrylic acid, 2%–10% polyethylene glycol diacrylate, 0.5%–5% recombinant collagen, 0.5%–5% boric acid, 0.1%–2% tannic acid, 0.1%–0.4% photoinitiator, and the balance being water.
[0010] The molecular weight of the polyethylene glycol diacrylate is 10,000 to 20,000.
[0011] The recombinant collagen has a molecular weight of 20–50 kDa.
[0012] The photoinitiator is one of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide, I2959, or lithium phenyl(2,4,6-trimethylbenzoyl)phosphate.
[0013] The preparation method of the antibacterial, antioxidant, self-adhesive three-network hydrogel is as follows:
[0014] Polyethylene glycol diacrylate and acrylic acid are dissolved in a photoinitiator solution, and then recombinant collagen, boric acid and tannic acid solutions are added sequentially and mixed evenly to obtain a prepolymer solution. After being irradiated with ultraviolet light, an antibacterial and antioxidant self-adhesive hydrogel is obtained.
[0015] The photoinitiator solution has a mass fraction of 0.1% to 1%.
[0016] The tannic acid solution has a mass fraction of 15% to 25%.
[0017] The UV lamp irradiation time is 5 to 10 minutes.
[0018] The present invention has the following beneficial effects:
[0019] 1) This invention employs acrylic acid and polyethylene glycol diacrylate (PEG) via free radical copolymerization to form a first network of the hydrogel, constituting the rigid portion of the three-network structure hydrogel. Recombinant collagen interpenetrates with the acrylic acid / PEG network, forming a second network of the hydrogel; this interpenetration enhances the rigidity of the hydrogel. Tannic acid and boric acid are bonded through borate ester bonds to form a third network. In the hydrogel of this invention, non-covalent interactions occur between tannic acid / boric acid, recombinant collagen, and acrylic acid / PEG diacrylate, dissipating energy under large deformations and endowing the hydrogel with excellent toughness. Therefore, the hydrogel of this invention exhibits strong wet adhesion and good extensibility.
[0020] 2) In the hydrogel system of this invention, boric acid endows the hydrogel with antibacterial properties; the addition of tannic acid, on the one hand, through dynamic borate ester bonds with boric acid, endows the hydrogel with self-healing properties; on the other hand, due to its abundant phenolic hydroxyl groups and superior biological properties, it further enhances the hydrogel's antibacterial activity and in vitro antioxidant capacity, and also endows the hydrogel with strong wet surface adhesion. Therefore, the composite three-network hydrogel of this invention has advantages such as outstanding adhesion performance, excellent biocompatibility, excellent extensibility, antibacterial and antioxidant properties, and is expected to be used as a wound dressing in a wider range of biomedical fields.
[0021] 3) The antibacterial and antioxidant self-adhesive hydrogel prepared by the present invention is prepared by a one-pot method, reacts at room temperature, is simple and quick to operate, requires a small amount of photoinitiator, and has no residual toxicity. Attached Figure Description
[0022] Figure 1 The mechanical test results of the adhesion properties of the hydrogels prepared in Examples 1-3 and Comparative Examples 1-3 are shown.
[0023] Figure 2 The results show the antioxidant properties of the hydrogels prepared in Examples 1-3 and Comparative Example 3. Figure 2 In (a), from left to right, are photographs of the hydrogels prepared in Comparative Example 3, Example 1, Example 2 and Example 3, which were incubated with DPPH solution for 30 min. Figure 2 In (b), from left to right, the DPPH scavenging rates of the hydrogels of Comparative Example 3, Example 1, Example 2 and Example 3 are respectively.
[0024] Figure 3The results show the antibacterial properties of the hydrogels prepared in Example 2, Comparative Example 2, and Comparative Example 3. A1-A4 represent the inhibitory effects of the blank sample, Comparative Example 2, Comparative Example 3, and the hydrogels prepared in Example 2 on *Escherichia coli*, respectively; B1-B4 represent the inhibitory effects of the blank sample, Comparative Example 2, Comparative Example 3, and the hydrogels prepared in Example 2 on *Staphylococcus aureus*, respectively.
[0025] Figure 4 The tensile properties of the hydrogels prepared in Examples 1-3 and Comparative Examples 1-3 are shown in the figure. Curve 1 represents the hydrogel material prepared in Example 1, curve 2 represents the hydrogel material prepared in Example 2, curve 3 represents the hydrogel material prepared in Example 3, curve 4 represents the hydrogel material prepared in Comparative Example 1, curve 5 represents the hydrogel material prepared in Comparative Example 2, and curve 6 represents the hydrogel material prepared in Comparative Example 3. Detailed Implementation
[0026] The technical solution of the present invention will be further described below with reference to specific embodiments, but these embodiments do not limit the present invention in any way. Unless otherwise specified, the embodiments use conventional reagents and conventional methods.
[0027] Example 1
[0028] 40 mg of polyethylene glycol diacrylate (PEGDA-20k) and 500 μL of acrylic acid (AAC) were dissolved in 1 mL of 0.5% I2959 solution. Then, 20 mg of recombinant collagen (COL) and 10 mg of boric acid (BA) were added and dissolved completely. Finally, 10 μL of 20% tannic acid (TA) solution was added to obtain a prepolymer solution. At room temperature, the prepolymer solution was poured into a polytetrafluoroethylene mold and irradiated with ultraviolet light for 10 min to obtain a highly adhesive antibacterial and antioxidant hydrogel.
[0029] Example 2
[0030] 40 mg of polyethylene glycol diacrylate (PEGDA-20k) and 500 μL of acrylic acid (AAC) were dissolved in 1 mL of 0.5% I2959 solution. Then, 20 mg of recombinant collagen (COL) and 10 mg of boric acid (BA) were added and dissolved completely. Finally, 20 μL of 20% tannic acid (TA) solution was added to obtain a prepolymer solution. At room temperature, the prepolymer solution was poured into a polytetrafluoroethylene mold and irradiated with ultraviolet light for 10 min to obtain a highly adhesive antibacterial and antioxidant hydrogel.
[0031] Example 3
[0032] 40 mg of polyethylene glycol diacrylate (PEGDA-20k) and 500 μL of acrylic acid (AAC) were dissolved in 1 mL of 0.5% I2959 solution. Then, 20 mg of recombinant collagen (COL) and 10 mg of boric acid (BA) were added and dissolved completely. Finally, 30 μL of 20% tannic acid (TA) solution was added to obtain a prepolymer solution. At room temperature, the prepolymer solution was poured into a polytetrafluoroethylene mold and irradiated with ultraviolet light for 10 min to obtain a highly adhesive antibacterial and antioxidant hydrogel.
[0033] Comparative Example 1
[0034] 40 mg of polyethylene glycol diacrylate (PEGDA-20k) and 500 μL of acrylic acid (AAC) were dissolved in 1 mL of 0.5% I2959 solution. The mixture was then introduced into a polytetrafluoroethylene mold at room temperature and irradiated with ultraviolet light for 10 min to obtain an adhesive hydrogel.
[0035] Comparative Example 2
[0036] 40 mg of polyethylene glycol diacrylate (PEGDA-20k) and 500 μL of acrylic acid (AAC) were dissolved in 1 mL of 0.5% I2959 solution, and 20 mg of recombinant collagen (COL) was added and mixed thoroughly. At room temperature, the mixture was poured into a polytetrafluoroethylene mold and irradiated with ultraviolet light for 10 min to obtain an adhesive hydrogel.
[0037] Comparative Example 3
[0038] 40 mg of polyethylene glycol diacrylate (PEGDA) and 500 μL of acrylic acid (AAC) were dissolved in 1 mL of 0.5% I2959 solution. 20 mg of recombinant collagen (COL) and 10 mg of boric acid (BA) were then added and mixed thoroughly. At room temperature, this mixture was poured into a polytetrafluoroethylene mold and irradiated with ultraviolet light for 10 min to obtain an adhesive antibacterial hydrogel.
[0039] Performance testing
[0040] (1) Adhesion performance test
[0041] The adhesion properties of the hydrogels prepared in Examples 1-3 and Comparative Examples 1-3 were tested.
[0042] Fresh pigskin was used to simulate human skin, and the adhesion properties of the hydrogel were evaluated using a shear test. A rectangular hydrogel sample (15mm × 15mm × 1mm) was adhered to the surfaces of two pigskin samples, pressed with a 700g weight for 10 minutes, and cured at room temperature for 2 hours. The adhesion properties were then tested using a universal testing machine. The samples were uniaxially stretched at a rate of 5mm / s until the pigskin separated from the hydrogel. The same experiment was repeated three times for each sample.
[0043] The results of the adhesion performance test are as follows Figure 1 As shown, PACBT-1 represents the hydrogel material prepared in Example 1, PACBT-2 represents the hydrogel material prepared in Example 2, PACBT-3 represents the hydrogel material prepared in Example 3, PA represents the hydrogel material prepared in Comparative Example 1, PAC represents the hydrogel material prepared in Comparative Example 2, and PACBT-0 represents the hydrogel material prepared in Comparative Example 3.
[0044] according to Figure 1 The results showed that the adhesion strength of the hydrogel materials prepared in Examples 1-2 was higher than that in Comparative Examples 1-3. With the increase of tannic acid solution addition, the adhesion performance of the hydrogel first increased and then decreased. The adhesion performance of Example 3 decreased because tannic acid has a polymerization inhibitory effect; as its content increases, it affects free radical polymerization, leading to a decrease in internal crosslinking density and thus a decrease in the adhesion strength of the hydrogel in Example 3. Example 2 showed the best adhesion performance, with an adhesion strength reaching 36.68 kPa.
[0045] (2) Antioxidant performance test
[0046] The antioxidant properties of the hydrogels prepared in Examples 1-3 and Comparative Example 3 were tested.
[0047] The antioxidant capacity of hydrogels was investigated using the DPPH free radical scavenging method. 50 mg of hydrogels with different components were dispersed in 2 mL of methanol, and 8 mL of 100 mM DPPH methanol solution was added. The mixture was incubated in the dark for 30 minutes. The reaction solution was scanned at a UV wavelength of 400-800 nm, and the absorbance at 515 nm was recorded. The blank was 2 mL of methanol without hydrogel mixed with 8 mL of DPPH solution. Each sample was measured in triplicate. The DPPH scavenging rate was calculated as follows:
[0048] Where A X A0 represents the absorbance of the DPPH solution and hydrogel sample at 515 nm after incubation for 30 min, while A0 represents the absorbance of the blank sample at 515 nm.
[0049] Figure 2 (a) Photographs from left to right of the hydrogels prepared in Comparative Example 3, Example 1, Example 2 and Example 3, respectively, incubated with DPPH solution for 30 min. Figure 2 (b) represents the DPPH removal rate of the hydrogels of Examples 1-3 and Comparative Example 3. PACBT-1 represents the hydrogel material prepared in Example 1, PACBT-2 represents the hydrogel material prepared in Example 2, PACBT-3 represents the hydrogel material prepared in Example 3, and PACBT-0 represents the hydrogel material prepared in Comparative Example 3.
[0050] Comparative Example 3 had no antioxidant properties, while Examples 1-3 had good antioxidant properties, with DPPH scavenging rates all above 60%. Moreover, the DPPH scavenging rate gradually increased with the increase of the amount of added tannic acid (TA), and the DPPH scavenging rate of Example 3 was as high as 86.68%.
[0051] (3) Antibacterial performance test
[0052] The antibacterial properties of Example 3, Comparative Example 2, and Comparative Example 3 were tested.
[0053] Staphylococcus aureus and Escherichia coli were selected as representatives of Gram-positive and Gram-negative bacteria, respectively, for in vitro antibacterial testing. The bacterial cultures stored at -80℃ were removed and brought to room temperature. 1 mL of the bacterial culture was added to 100 mL of sterilized LB broth. The inoculated Erlenmeyer flasks were then incubated overnight at 37℃ and 120 rpm using a shaker. 200 μL of the overnight culture was transferred to a 96-well plate, and its OD600 value was measured using a microplate reader. Through continuous dilution, a concentration of 1 × 10⁻⁶ was obtained. 8 CFU mL -1 The bacterial culture (OD600 = 0.12-0.16) was then diluted 10... 2 The concentration was increased by 1×10 times, resulting in a concentration of 1×10. 6 CFU mL -1 Prepare the bacterial solution for later use.
[0054] Take 0.2g of hydrogel sample that has been sterilized overnight under UV light and add it to a 10mL PV tube. Add 5mL of a 1×10⁻⁶ solution. 6 CFU mL -1 The bacterial culture was incubated at 37℃ and 120 rpm for 4 hours. 0.2 g of sterile water was used as a blank control, and 5 mL of a 1×10⁻⁶ solution was added. 6 CFU mL -1 Co-culture with bacterial culture. Take 20 μL of the co-cultured bacterial culture and dilute it 10... 2 Dilute the bacterial suspension by 50 μL and spread it onto agar plates. Incubate the plates in an incubator for 18 hours and observe the colony count on each plate. Spread each sample onto 3 plates.
[0055] Figure 3The results show the inhibitory effects of the hydrogels prepared in the blank sample, Example 2, Comparative Example 2, and Comparative Example 3 on *Escherichia coli* and *Staphylococcus aureus*. Specifically, A1-A4 represent the inhibitory effects of the hydrogels prepared in the blank sample, Example 2, Comparative Example 2, and Comparative Example 3 on *Escherichia coli*, while B1-B4 represent the inhibitory effects of the hydrogels prepared in the blank sample, Example 2, Comparative Example 2, and Comparative Example 3 on *Staphylococcus aureus*. The results indicate that Comparative Example 2 had no inhibitory effect on *Escherichia coli* and *Staphylococcus aureus*, while Comparative Example 3 showed a relatively significant inhibitory effect. The inhibitory effect was significantly improved after the addition of tannic acid, and the antibacterial rate of Experiment 2 approached 100%.
[0056] (4) Tensile property test
[0057] The hydrogel materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to tensile tests.
[0058] Axial tensile tests were performed on the hydrogel using a universal testing machine. The hydrogel was prepared into a strip measuring 60 mm × 20 mm × 1 mm, with an initial clamping distance of 30 mm. The tensile rate was set to 50 mm / min, and the sample was stretched until fracture. The experiment was conducted at room temperature. The tensile strength (δ, kPa) was calculated using the following formula:
[0059] Where F is the destructive load (N); l is the initial width of the hydrogel (mm); and d is the initial thickness of the hydrogel (mm).
[0060] The results of the tensile property test are as follows Figure 4 As shown, 1 represents the hydrogel material prepared in Example 1, 2 represents the hydrogel material prepared in Example 2, 3 represents the hydrogel material prepared in Example 3, 4 represents the hydrogel material prepared in Comparative Example 1, 5 represents the hydrogel material prepared in Comparative Example 2, and 6 represents the hydrogel material prepared in Comparative Example 3.
[0061] Depend on Figure 4 It can be seen that the elongation of the hydrogel materials prepared in Examples 1-3 is higher than that in Comparative Examples 1-3, and can be stretched to 15-22 times the original length. They have excellent extensibility and can be applied to joint wounds with large mobility, providing complete wound closure and becoming a barrier against bacterial infection.
Claims
1. An antibacterial, antioxidant, self-adhesive three-network hydrogel, characterized in that: The first network is formed by copolymerizing acrylic acid and polyethylene glycol diacrylate, the second network is formed by interpenetrating recombinant collagen, and the third network is formed by bonding tannic acid and boric acid through borate ester bonds. It is made from the following components in the indicated mass ratios: 30%–35% acrylic acid, 2%–10% polyethylene glycol diacrylate, 0.5%–5% recombinant collagen, 0.5%–5% boric acid, 0.1%–2% tannic acid, 0.1%–0.4% photoinitiator, and the balance being water.
2. The antibacterial, antioxidant, self-adhesive three-network hydrogel according to claim 1, characterized in that: The molecular weight of the polyethylene glycol diacrylate is 10,000 to 20,000; The molecular weight of the recombinant collagen is 20–50 kDa; The photoinitiator is one of ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 2,2'-azo (2-methyl-N-(2-hydroxyethyl)propionamide), I2959, or lithium phenyl (2,4,6-trimethylbenzoyl)phosphate.
3. The method for preparing the antibacterial, antioxidant, self-adhesive three-network hydrogel according to claim 1, characterized in that... The preparation steps are as follows: Polyethylene glycol diacrylate and acrylic acid are dissolved in a photoinitiator solution, and then recombinant collagen, boric acid and tannic acid solutions are added sequentially and mixed evenly to prepare a prepolymer solution. After being irradiated with ultraviolet light, an antibacterial and antioxidant self-adhesive hydrogel is obtained. The mass concentration of the photoinitiator solution is 0.1% to 1.0%; The mass fraction of the tannic acid solution is 15% to 25%. The ultraviolet light irradiation time is 5 to 10 minutes.
4. The application of the antibacterial, antioxidant, self-adhesive three-network hydrogel of claim 1 in the preparation of wound treatment materials.
Citation Information
Patent Citations
Polyelectrolyte double-network hydrogel for healing of bacterial infection wound and preparation method and application of polyelectrolyte double-network hydrogel
CN115626995A
Tannic acid coated nanocellulose / polyacrylic acid adhesive hydrogel and preparation method thereof
CN112266486A
Hydrogel dressing capable of promoting wound healing
CN113274542A